2023
DOI: 10.1002/ange.202218799
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Enhancement and Quenching in Single‐Molecule Tip‐Enhanced Raman Spectroscopy

Abstract: Despite intensive research in surface enhanced Raman spectroscopy (SERS), the influence mechanism of chemical effects on Raman signals remains elusive. Here, we investigate such chemical effects through tip‐enhanced Raman spectroscopy (TERS) of a single planar ZnPc molecule with varying but controlled contact environments. TERS signals are found dramatically enhanced upon making a tip–molecule point contact. A combined physico‐chemical mechanism is proposed to explain such an enhancement via the generation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Here, we perform UHV-TERS experiments at an open-shell molecule, which provides an ideal playground for revealing the complex interplay among the charge, spin, and electronic states of a molecule in a nanocavity and its impact on the optical properties. It has been shown that a controlled atomic contact between the STM tip and molecules leads to a dramatic rise of Raman intensity, which is a clear indication of enhancement beyond the electromagnetic field intensification. Therefore, we select a highly tunable single-molecule break-junction system that exhibits a reversible transition between a mixed-valence state and a singly charged radical upon decoupling from a metal substrate. We manipulate a single perylene-3,4,9,10-tetracarboxylic dianhydride (PTCDA) molecule on Ag(111) while simultaneously measuring the electronic spin state and the Raman spectra in the chemical enhancement mode.…”
mentioning
confidence: 99%
“…Here, we perform UHV-TERS experiments at an open-shell molecule, which provides an ideal playground for revealing the complex interplay among the charge, spin, and electronic states of a molecule in a nanocavity and its impact on the optical properties. It has been shown that a controlled atomic contact between the STM tip and molecules leads to a dramatic rise of Raman intensity, which is a clear indication of enhancement beyond the electromagnetic field intensification. Therefore, we select a highly tunable single-molecule break-junction system that exhibits a reversible transition between a mixed-valence state and a singly charged radical upon decoupling from a metal substrate. We manipulate a single perylene-3,4,9,10-tetracarboxylic dianhydride (PTCDA) molecule on Ag(111) while simultaneously measuring the electronic spin state and the Raman spectra in the chemical enhancement mode.…”
mentioning
confidence: 99%